Exploiting Transmit Buffer Information at the Receiver in Block-Fading Channels. (20th August 2008) - Rajan Rajan, Dinesh Dinesh
Abstract : It is well known that channel state information at the transmitter (CSIT) leads to higher throughput in fading channels. We motivate the use of transmit buffer information at receiver (TBIR). The thesis of this paper is that having partial or complete instantaneous TBIR leads to a lower packet loss rate in block-fading channels assuming the availability of partial CSIT. We provide a framework for the joint design and analysis of feedback (FB) and feed-forward (FF) information in fading channels. We then introduce two forms of TBIR—statistical and instantaneous—and show the gains of each form of TBIR using a heuristic scheme. For a Rayleigh fading channel, we show that in certain cases the packet error rate reduces by nearly an order of magnitude with just one bit of feed-forward information of TBIR.